2020
DOI: 10.1111/1754-9485.13031
|View full text |Cite
|
Sign up to set email alerts
|

Quality and access – Early experience of implementing a virtual stereotactic chart round across a national network

Abstract: Introduction Stereotactic radiation therapy is a highly specialised technique which requires careful and structured implementation. As part of a national stereotactic programme implementation, protocols were developed and a national stereotactic chart round was formed, which strongly recommended attendance and presentation of all cases before treatment. Herein, we describe our experiences launching a national chart round and its importance in a stereotactic programme. Method Stereotactic chart rounds were held… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Data regarding the impact of peer review on SBRT planning are limited to two smaller cohorts from time periods in which SBRT utilisation was less frequent, and another more recent cohort of 285 cases. [10][11][12] Suggested plan changes from peer review are variably reported in the literature, but commonly are categorised as major changes which require repeat planning and minor changes which do not. [13][14][15][16] A previous review found that suggested plan changes occur in 10% of all cases, with higher rates of change observed for stereotactic radiotherapy and several specific cancer subsites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data regarding the impact of peer review on SBRT planning are limited to two smaller cohorts from time periods in which SBRT utilisation was less frequent, and another more recent cohort of 285 cases. [10][11][12] Suggested plan changes from peer review are variably reported in the literature, but commonly are categorised as major changes which require repeat planning and minor changes which do not. [13][14][15][16] A previous review found that suggested plan changes occur in 10% of all cases, with higher rates of change observed for stereotactic radiotherapy and several specific cancer subsites.…”
Section: Discussionmentioning
confidence: 99%
“…10 A report of stereotactic radiotherapy cases in Australia found suggested plan changes in 22.3% of cases, though the rate of implementation of changes was unclear. 12 A 2015 singleinstitution study of 513 SBRT cases found that changes were implemented in 22.6% of cases, with lower rates of change in higher-volume subsites including liver (18%) and lung (17%) cases. 11 The proportion of suggested changes which were not implemented was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Several forms of hybrid MDTs have, however, been studied, mostly using videoconferencing for reasons of convenience or geography. 23,[33][34][35][36][37][38][39][40] These meetings require multisite coordination with available technology at all sites. 39 Moreover, expertise is often not available on demand, as these (bi-) weekly meetings need to be scheduled ahead to ensure simultaneous presence of key members.…”
Section: Discussionmentioning
confidence: 99%
“…Icon Cancer Centre reported their experience with virtual national stereotactic chart rounds held across Australia and New Zealand via videoconference. 32 Twenty-one radiation oncology facilities were credentialed to increase the availability of stereotactic treatment and ensure consistent practice, education and positive clinical outcomes. An increasing number of yearly cases presented per radiation oncologist (RO) were associated with lower rates of recommended changes.…”
Section: The Importance Of and Evidence For Peer Review In Radiation ...mentioning
confidence: 99%
“…In Australia and internationally, peer review has been reported to improve patient care both directly and indirectly and be feasible within radiation oncology facilities 6–35 . The American Society for Radiation Oncology (ASTRO) surveyed members in 2013 to establish peer review practice patterns, 36 with the majority of the 572 participating physicians supporting formal recommendation and guidance on peer review.…”
Section: Introductionmentioning
confidence: 99%